Distribusi Pertanyaan Higher Order Thinking Skill (HOTS) pada Buku Teks Bahasa Indonesia SMP/MTs Kelas VIII Kurikulum 2013 - Intan Permatasari (Nuances of Indonesian Language, 2021)
This study aims to: (1) find out the balance of HOTS questions between types of texts in Indonesian textbooks SMP/MTs class VIII 2013 curriculum, (2) find out the balance of questions between cognitive levels in Indonesian textbooks SMP/MTs class VIII 2013 curriculum. This type of is quantitative descriptive. The population in this study were all Indonesian textbooks in class VIII SMP/MTs used in learning with the 2013 curriculum. As for the sample used in this study were Indonesian textbooks for SMP/MTs class VIII 2013 curriculum namely, (1) title: proficient in Indonesian, vol. class VIII SMP/MTs; (2) compiler: educative team; (3) editor: Muhammad Baihaqi, S.S.; (4) publisher: Erlangga. The instruments in this research in the documentation study and recording guidelines. This results of the study conclude: (1) HOTS questions between cognitive levels, i.e. analyzing more found questions (2) HOTS questions among types of text, news texts and persuasion texts are the same number of questions found, slogan and poster ad text, exposition text, fiction and non fiction text found, explanatory texts and review texts are the same number of questions found, drama texts and poetry texts found the most questions.